Adapting to climate change through play? Didactically effective elements of a business simulation game - Fischer, Sophie; Göhlich, Michael; Schmitt, Jan (Frontiers in Education, 2024)
The negative consequences of climate change are widespread and have a global impact. An industrialized region of Germany must adapt to the effects of climate change and comply with political regulations. Previous studies indicate that economic actors who are not directly affected by climate change approach climate change mitigation and adaptation primarily based on legal requirements and often feel discouraged by the absence of data-based reports. Addressing this challenge, game-based learning emerges as a promising pathway. To examine game-based learning's applicability and potential for climate adaptation, we developed a business simulation game, simultaneously identifying didactically effective elements for managers who would participate in it. Using expert interviews and focus groups, we conducted a qualitative study with three HR developers from larger companies and nine managers and founders of start-ups to develop a business simulation game on climate adaptation. We discussed common human resource development measures in companies and compared them with more innovative approaches such as a simulation game. Based on the Grounded Theory methodology, theoretical coding was used to analyze the qualitative data. The results indicate that personnel development in companies is evolving in response to economic changes. Individual resources such as motivation (especially for managers), personnel and time play a crucial role in establishing a business game as an educational offering. The identified game elements can also be used theoretically and practically in the development of other educational games.